Enhancing Students’ Speaking Skill through Video Dubbing Project - Sulastri Manurung; Albert Efendi Pohan (UICELL, 2019)
This study aimed to describe the implementation of video dubbing project and to find out the enhancement of the students’ speaking skill after the implementation of video dubbing project in teaching speaking of fourth semester students UNRIKA in academic year 2018-2019. Action research procedures (including planning, action, observation, reflection) were used to study the progress and subject outcomes. The study was conducted in two cycles which was held from February to July 2019. The researcher was assisted by another lecturer to observe and assist the implementation of video dubbing project. Data were collected through observer sheet and test. Data obtained from cycle 1 were analysed and used for revision and improvement in cycle 2. Then, data obtained from cycle 2 were presented as the outcomes of the project. The test result revealed that students speaking skill was improved. The improvement was particularly seen in pronunciation. The mean score of the students in pre-test was 67.02. After the implementation of the project on cycle 1, the students mean score was 83.63 and on cycle 2 was 90.61. During the implementation, students were motivated, enthusiastic, active, and eager to work together and show positive attitude towards the language learning. Keywords: video dubbing, enhancement, speaking skill